THU0493 Association of the Toll-Like Receptor 4 (TLR4) Gene with Gout. (10th June 2014) - Merriman, T.; Topless, R.; Day, R.; Kannangara, D.; Williams, K.; Bradbury, L.; Brown, M.; Harrison, A.; Hill, C.; Jones, G.; Lester, S.; Littlejohn, G.; et al.
Abstract : Background: Gout results from innate immune response to monosodium urate (MSU) crystals that form when serum urate is elevated. Identification of genetic risk factors for hyperuricemia and the MSU immune response is therefore important for insight into the etiology of gout. Whilst genome-wide association studies have provided significant insights into the causes of hyperuricemia there are no confirmed loci for non-serum urate pathways in gout. Recently association of the rs2149356 variant in the TLR4 locus with gout was reported in a Chinese sample set (odds ratio TT genotype =1.88, P =8x10 –5 ) 1 . TLR4 triggers innate immune response to endogenous ligands, including MSU crystals 2 . Objectives: To test rs2149356 for association in European and New Zealand (NZ) Polynesian gout case-control sample sets. Methods: All gout cases were clinically ascertained according to the American Rheumatism Association criteria. European cases (n=1606) were recruited from New Zealand (n=599), by the Eurogout consortium within the European Crystal Network (n=784) and by the Arthritis Genomics Recruitment Initiative in Australasia (AGRIA; n=223). European non-gouty controls (n=8066) were recruited from NZ (n=875) and sourced from the Atherosclerosis Risk in Communities (n=4144) and Framingham Heart (n=3047) studies. There were 872 New Zealand Maori and Pacific Island (Polynesian) cases and 1088 controls. Genotyping was done by Taqman and statistical analysis by STATA. Results: Using unstratified controls the T allele, but not the TT genotype, was associated with gout in Europeans (ORTallele =1.09, P =0.05; ORTTgenotype =1.15, P =0.13). There was no evidence for association in Polynesians (ORTallele =0.90, P =0.12; ORTTgenotype =0.88, P =0.31). However, comparison of cases to hyperuricemic controls strengthened evidence for association with gout in Europeans (ORTallele =1.18, P =0.004; ORTTgenotype =1.38, P =0.017), but made no difference in Polynesians (ORTallele =, P =0.30; ORTTgenotype =0.87, P =0.47). Conclusions: The previous report of association of TLR4 with gout in Chinese was replicated in Europeans but not Polynesians. Strengthening of association using hyperuricemic controls is consistent with a role for this locus in gouty inflammation in the presence of hyperuricemia. Subject to further replication, TLR4 represents the first non-serum urate genetic risk locus identified in gout, and provides support for a role of TLR4 in etiology. References: Qing et al. PLoS One 2013;5:e64845. Liu-Bryan et al. Arthritis Rheum 2005;52:2936 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4781